The role of age in the physiological adaptations and psychological responses in bikini-physique competitor contest preparation: a case series - Daniel E. Newmire; Heather E. Webb (Taylor & Francis Group, 2021)
The increased popularity of the bikini-physique competitions has not translated to greater research identifying the influence of age on adaptations during contest preparation. The purpose of this case series was to observe how age may influence the adaptations normally seen during preparation and the exploration of newer protocols to address adaptations more relative to the judging standards. Over a 16-week pre-contest preparation, a 32-y bikini competitor (BC) and 44-y master's bikini competitor (MBC) visited the laboratory bi-weekly to observe changes in body fat mass (BF), lean body mass (LBM), bone mineral density (BMD), total body water (TBW); exploratory measures of deltoid cross-sectional area (DeltCSA), gluteus maximus muscle thickness (GMMT), and subcutaneous adipose tissue thickness (SAT); reproductive hormones estradiol (E2), luteinizing hormone (LH), and energy balance hormones triiodothyronine (T3), leptin and ghrelin; hydration status during contest preparation and the week of competition; resting metabolic rate (RMR); psychometric data related to perceived anxiety, stress, and body image were assessed. No differences between BC and MBC were observed in BF, LBM, BMD, and TBW. Both competitors showed a small loss in LBM. Both BC and MBC showed a contrasting increase in DeltCSA and a loss in GMMT. MBC showed to be slightly more dehydrated (1.025 vs 1.021 g·mL− 1) than BC. Both competitors maintained a euhydration status the day of the competition. No time differences were found between BC and MBC during RMR. BC showed a higher mean difference RMR compared to MBC (2.66 ± 0.75 kcal·kgLBM− 1·d− 1). MBC showed a higher mean difference in LH concentration (84.6 ± 6.01 IU·L− 1), which may be explained by perimenopausal status. MBC had a higher mean difference concentration of leptin (2.51 ± 0.24 ng·mL− 1·kgFM− 1), which was unperturbed by fat loss may be interrelated LH. BC self-reported a higher mean energy intake (15.07 ± 3.43 kcal·kgLBM− 1·d− 1) and higher aerobic training volume (93.26 ± 40.68 min·d). BC and MBC showed similar composition changes, slightly differing metabolic rates, and differing hormonal LH and leptin responses. This finding is in contrast to previous work showing both LH inhibition and leptin diurnal disturbance in younger, female athletes with low energy availability. The exploratory measures may have some benefit for bikini-physique competitors related to the judging criteria. Age did not seem to play a role in contest preparation adaptations.